2018
DOI: 10.1074/jbc.ra118.002514
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of human C-terminal binding protein (CtBP) into tetramers

Abstract: C-terminal binding protein 1 (CtBP1) and CtBP2 are transcriptional coregulators that repress numerous cellular processes, such as apoptosis, by binding transcription factors and recruiting chromatin-remodeling enzymes to gene promoters. The NAD(H)-linked oligomerization of human CtBP is coupled to its co-transcriptional activity, which is implicated in cancer progression. However, the biologically relevant level of CtBP assembly has not been firmly established; nor has the stereochemical arrangement of the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 47 publications
7
65
1
Order By: Relevance
“…Although previous studies have proposed dimeric CtBP as the relevant oligomeric state (Nardini et al, 2003;Thio et al, 2004;Nardini et al, 2009;Bi et al, 2018;Mani-Telang et al, 2007;Dcona et al, 2019), our studies with multi-angle light scattering and sitedirected mutagenesis have shown that the primary effect of NADH binding is to promote the assembly of two CtBP dimers into tetramers (Bellesis et al, 2018). This was further supported by the observation that CtBP1 and CtBP2 exhibit similar tetrameric assemblies within distinct crystal lattices used for structure determination (Hilbert et al, 2014), resulting in a tetramer model for CtBP.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Although previous studies have proposed dimeric CtBP as the relevant oligomeric state (Nardini et al, 2003;Thio et al, 2004;Nardini et al, 2009;Bi et al, 2018;Mani-Telang et al, 2007;Dcona et al, 2019), our studies with multi-angle light scattering and sitedirected mutagenesis have shown that the primary effect of NADH binding is to promote the assembly of two CtBP dimers into tetramers (Bellesis et al, 2018). This was further supported by the observation that CtBP1 and CtBP2 exhibit similar tetrameric assemblies within distinct crystal lattices used for structure determination (Hilbert et al, 2014), resulting in a tetramer model for CtBP.…”
mentioning
confidence: 51%
“…Oligomerization is essential for CtBP transcriptional activity, with CtBP forming dimers (Kumar et al, 2002;Nardini et al, 2003) and higher order structures (Bellesis et al, 2018;. Binding of NAD(H) promotes oligomerization of CtBP2, which is required for transcriptional activities (Kumar et al, 2002;Zhang et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, previous studies have shown that CtBP polymerization contributes to its regulatory effects, and CtBP dimerization is regulated by cellular NADH binding to its conserved dehydrogenase domain 52,53 . Pharmacologic reduction of NADH depolymerizes CtBP, resulting in induction of certain normally repressed target genes 54,55 . Since CtBP dimers can be disrupted not only by reduction in NADH level, but also by small molecule CtBP dehydrogenase inhibitors 56 , a promising approach for treatment of HGSOC and other CtBP dependent cancers that is currently under investigation may be combining small molecule CtBP inhibition with strategies that reduce cellular NADH level 57 .…”
Section: Discussionmentioning
confidence: 99%
“…As it is well acknowledged that tumor cells often exert raised NADH levels owing to NADH production underneath hypoxic and pseudohypoxic environments [13][14][15]. A previous study have implied that NADH can interact CtBP with a high affinity, contribute to a modification in the protein structure that empowers its communication with transcriptional suppressors [16][17][18]. Moreover, it has been suggested that high NADH levels under hypoxic environments lead to an abridged E-cadherin expression level in tumors cells, contribute to the oncogenic role of CtBP in human manligancies [19].…”
Section: Introductionmentioning
confidence: 99%